Pericentral hydroxychloroquine retinopathy in a Caucasian female - Anand, Nikhil (Am J Ophthalmol Case Rep, 2018)
PURPOSE: To report a rare presentation of the pericentral pattern of hydroxychloroquine (HCQ) retinal toxicity in a Caucasian female. OBSERVATIONS: The patient presented with 20 years of exposure to HCQ, at a daily dose of 5.2mg/kg of actual body weight, and manifested a pericentral-only phenotype of HCQ toxicity, as demonstrated with detailed structural and functional testing. CONCLUSIONS AND IMPORTANCE: Although rare, the pericentral pattern of HCQ toxicity may occur in Caucasian patients in the absence of paracentral changes.